Implementasi Metode Scramble dalam Meningkatkan Kemampuan Membaca Permulaan Huruf Braille pada Anak Tunanetra Kelas I di SLB Negeri Muara Bulian - Asih, Rini; Rahmahtrisilvia, Rahmahtrisilvia (Jurnal Penelitian Pendidikan Khusus, 2022)
In this classroom action research the author is interested in focusing on the title "Implementation of the Sramble Method in Improving the Ability to Read Beginning of Braille in Class I Blind Children at SLB Negeri Muara Bulian". The action was carried out in 2 cycles where each cycle had 4 meetings. The total of all meetings in this study were 8 meetings which were divided into several stages of planning, action, observation and reflection. At the time of the research, subject A had the initial ability to read the beginning with a value of 35, in the first cycle the score was 65 and in the second cycle the score was 90. at SLB Negeri Muara Bulian has increased.